Three-Dimensional Fault Model and Activity in the Arc-Shaped Tectonic Belt in the Northeastern Margin of the Tibetan Plateau - Li, Liguo; Li, Zhigang; Sun, Chuang; Wang, Weitao; Dai, Xiangming; Zhang, Yipeng; Liang, Hao; Xu, Binbin; Wu, Xiancan; Lv, Liangwei (Frontiers in Earth Science, 2022)
The arc-shaped tectonic belt, located in the northeastern margin of the Tibetan Plateau, is one of the leading edges of the plateau's outward growth and uplift expansion, with a large number of active faults and frequent seismic activity. Researchers have carried out numerous studies on active faults in this region, and a wealth of reliable basic data has been accumulated. However, integrating multidisciplinary data to establish a 3D geometrical structure model that is concerned about seismogenic tectonics and can be tested, has become the key to restricting the regional seismic hazard evaluation. Based on a series of published active tectonic research, we analyze in detail the surface and deep coupling relationships of the major active faults in this region and establish three sets of 3D fault structure models, which are built respectively by active fault mapping and dip angles (the V1 model), 7 magnetotelluric profiles and 7 auxiliary profiles (the V2 model), and multi-source data (the V3 model) and continuously close to the real geological facts. From the model perspective, it is suggested that the controversial Haiyuan fault is a crustal-scale left-slip fault and the shape of the Liupanshan fault reflects the absorption of the left-slip component of the Haiyuan fault. Comparing the same fault plane of these three models, we find that the V3 model is more consistent with geological facts, showing that by assisting the multi-source data 3D geological modeling technique we can establish a 3D geological model closest to the real regional structure. Finally, combining the V3 model, the fault segmentation, and the empirical formulas of the moment magnitude-rupture parameters, we segment the faults and calculate the potential moment magnitudes of the major active faults in the study region. The faults with relatively higher seismic hazards are the Liupanshan fault, the southeastern segment of the Xiangshan-Tianjingshan fault, the westernmost segment of the Haiyuan fault, and the West Qinling fault, of which the estimated potential moment magnitudes are generally more than 7.0. Our study provides a referenced 3D geological model for exploring the deep structures of the region, regional geological research, and earthquake disaster prevention.